4x+10=10x+7

Simple and best practice solution for 4x+10=10x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+10=10x+7 equation:


Simplifying
4x + 10 = 10x + 7

Reorder the terms:
10 + 4x = 10x + 7

Reorder the terms:
10 + 4x = 7 + 10x

Solving
10 + 4x = 7 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
10 + 4x + -10x = 7 + 10x + -10x

Combine like terms: 4x + -10x = -6x
10 + -6x = 7 + 10x + -10x

Combine like terms: 10x + -10x = 0
10 + -6x = 7 + 0
10 + -6x = 7

Add '-10' to each side of the equation.
10 + -10 + -6x = 7 + -10

Combine like terms: 10 + -10 = 0
0 + -6x = 7 + -10
-6x = 7 + -10

Combine like terms: 7 + -10 = -3
-6x = -3

Divide each side by '-6'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 3x^3-35x^2+122x-120=0 | | 11y-10g-22=13 | | 18+z=37 | | 14-7x=.245 | | Log(x)=6.2 | | (x+6)(x-6)=B | | 97/(1-.3) | | 14+7x=.245 | | 120/(1-.3) | | 8x-(5x-7)=25 | | 171.34=120/(1-m) | | 100=75/(1-m) | | -3m+11=-6+5+4m | | 2(3(4)-1)-3(4(4)+3)-6=5x-4(4x-1) | | 120/1-51.34 | | 171.34-120/1-m | | 12m+23=179 | | 2(3x-1)-3(4x+3)-6=5x-4(4x-1) | | -92+7b=13 | | 9y+3=6(y-7) | | 9/10/69 | | -6(x+4)+4x+7=7x+9 | | 47+13a=164 | | 4w-13=47 | | 25x+35y=6 | | 25x-78=72 | | 8(5s-12)-16(2s+7)=0 | | 5x-(x-3)=-21 | | d/8*-4=-6 | | 14x^2-17=0 | | 38=6(y+7)-8y | | 2x-19=73 |

Equations solver categories